PERKEMBANGAN KONSEP RAHN DALAM PEGADAIAN - Khoirunnazilah, Khoirunnazilah; Nurwanti, Nurwanti; Larasati, Ayu (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2022)
The development of the Rahn Concept in Sharia Pawnshops in Indonesia is relevant for further research. With this study, it will be known how to analyze public interest in using Sharia Pawnshops. The aim of this research is to analyze the development of the concept of rahn in pawnshops. The research to be carried out is library research, namely by collecting data related to the themes discussed. Understanding Sharia Pawnshops In Arabic terms, pawns are termed rahn and can also be named al-hasbu. The amount of the loan is determined by the pawnshop, depending on the value and amount of the pawned goods. Etymologically, the meaning of rahn is permanent and long, while al- hasbu means the detention of an item with rights so that it can be used as payment for the item. The services and products offered by sharia pawnshops are: Providing loans or financing on the basis of the law of pawning, Providing loans or financing on the basis of the law of pawning, Custody of goods (ijarah), Gold counters. Many people who pawn their goods in the form of gold to be used as business capital in investing. The customer pays off the pawned goods according to the contract: full repayment, re-pawning, installments, or partial redemption. Keywords: Sharia Pawnshops, Public Interest, Sharia Pawnshop Products